Geomorfologia e neotectônica no Vale do Apodi-Mossoró RN - Maia, Rúbson Pinheiro (2012)
Numerous studies have indicated that the Potiguar Basin is affected by Cenozoic tectonics. The reactivation of Cretaceous fault systems affect the post-rift units, witch include Neogene and overlying Quaternary sediments. In this context, the objectives of this thesis are the followings: (1) to characterize the effects of post-rift tectonics in the morphology of Apodi Mossoró-river valley located in the central portion of the Potiguar, (2) to characterize the drainage of the Apodi Mossoró river valley and investigate the behavior of their channels across active faults, and (3) to propose a geologic-geomorphological evolutionary model for the study area. This study used a geological and geomorphological mapping of the central part of the basin, with emphasis on the Quaternary record, luminescence dating of sediments, and geoelectric profiles of the area. The results reveal by maps of structural lineaments and drainage channels of the rivers form valleys that are affected by faults and folds. In Apodi-Mossoró valley, anomalies of channel morphology are associated with the deformation of the post-rift basin. These anomalies show the reactivation of major fault systems in the Potiguar Basin in Cenozoic. On a regional scale, can be seen through the vertical electric profiles that the Cenozoic tectonics is responsible for the elevation of a macro dome NE-SE-trending 70-km long and 50km wide and up to 270 above sea level. In this sector, the vertical electric profiles data show that the contact between the Cretaceous and Neogene rise more than 100m. This Is an important feature of inversion data obtained in this work showed that the deposits that cover the macro dome (Serra do Mel) have ages of 119 ka to 43 ka. In the river valley and surrounding areas Apodi-Mossoró ages vary between 319 ka and 2.7 ka. From these data it was possible to establish the correct geochronological posiconamento paleodepósitos of distinguishing them from the fluvial deposits of the Neogene (Barreiras Formation)